Discrete Value Distribution with Weight for the Periodic Hurwitz Zeta-Function - Žalytė, Ieva; Kačinskaitė, Roma (Jaunųjų mokslininkų darbai, 2017)
In the paper, we prove the discrete limit theorem with weight for the periodic Hurwitz zeta-function ζ(s, α; a) with a transcendental parameter α, 0 < α ≤ 1, in the complex plane when the weight function w(l) is used.